Land Regulations in the Yogyakarta Sultanate Rijksblad In the Second Decade of the 20 Century - Setiawati, Nur Aini (Paramita: Historical Studies Journal, 2021)
Abstract: Land regulations are made to organize life together in the community hoping that there are regulations that can provide legal certainty and resolve agrarian conflicts. However, in feudal times, the theory of royal property (vorstendomein) and royal property rights (vorsteneigendoormsrecht) said that all royal lands belonged to the king. Since the signing of the Giyanti treaty in 1755, the Sultan has made rules to regulate life in the communities enshrined in Rijksblad. Therefore, it is necessary to study land regulations during feudal times as part of the history of legal changes and developments in Yogyakarta society. Using the historical research method and the law approach through the Rijksblad, this research shows that even though the land regulations in the feudal era said that the king was the absolute owner of the land, the Sultan had made the rules.Abstrak: Pengaturan pertanahan dibuat untuk menata kehidupan bersama dalam masyarakat dengan harapan ada regulasi yang dapat memberikan kepastian hukum dan menyelesaikan konflik agraria. Namun, pada zaman feodal teori kepemilikan kerajaan (vorstendomein) dan hak milik kerajaan (vorsteneigendoormsrecht) mengatakan bahwa semua tanah kerajaan adalah milik raja. Sejak penandatanganan perjanjian Giyanti pada tahun 1755, Sultan telah membuat aturan untuk mengatur kehidupan masyarakat yang diabadikan di Rijksblad. Oleh karena itu, perlu dikaji regulasi pertanahan pada masa feodal sebagai bagian dari sejarah perubahan dan perkembangan hukum di masyarakat Yogyakarta. Dengan menggunakan metode penelitian sejarah dan pendekatan hukum melalui Rijksblad, penelitian ini menunjukkan bahwa meskipun peraturan pertanahan pada zaman feodal menyatakan bahwa raja adalah pemilik mutlak atas tanah, namun yang dibuat oleh Sultan adalah peraturannya.Ã‚Â